2020
DOI: 10.1094/pdis-10-19-2116-re
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Adult-Plant Resistance to Stripe Rust in Common Wheat (Triticum aestivum)

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici, is a globally devastating disease of common wheat (Triticum aestivum L.), resulting in substantial economic losses. To identify effective resistance genes, a genome-wide association study was conducted on 120 common wheat lines from different wheat-growing regions of China using the wheat 90K iSelect SNP array. Seventeen loci were identified, explaining 9.5 to 21.8% of the phenotypic variation. Most of these genes were detected in the A (seven) and B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…More than 80 of these QTLs were identified using GWAS [5], and many were identified in field trials, suggesting that they may confer APR. Numerous additional QTLs for APR to Pst have been detected since 2017 [30][31][32][33]66]. We aligned the APR GWAS results with those QTLs reported in the QTL reviews of Wang and Chen (2017) and Jan et al (2021) (Figure S9) [5,6].…”
Section: Adult Plant Resistancementioning
confidence: 59%
See 1 more Smart Citation
“…More than 80 of these QTLs were identified using GWAS [5], and many were identified in field trials, suggesting that they may confer APR. Numerous additional QTLs for APR to Pst have been detected since 2017 [30][31][32][33]66]. We aligned the APR GWAS results with those QTLs reported in the QTL reviews of Wang and Chen (2017) and Jan et al (2021) (Figure S9) [5,6].…”
Section: Adult Plant Resistancementioning
confidence: 59%
“…This study detected ASR-associated loci for stripe rust resistance. In cultivated wheat, many GWAS have been completed, yielding more than 80 QTLs that can be used in marker-assisted selection [5,[29][30][31][32][33]. Most of the GWAS for adult plant stripe rust resistance in wheat used single-locus association algorithms that may not capture the multi-locus complexity of agronomic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified many APR QTLs on all of the wheat chromosomes and proposed some meta‐QTLs on the chromosomes of 1B, 2A, 2B and 4B (Pal et al, 2022; Tomar et al, 2021; Wu et al, 2021; Yang et al, 2020; Yao et al, 2021). In this study, all the QTLs had a similar or close physical chromosomal location to that of previously reported QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Qyr‐1B . 1 was located in a hot region that has been identified in many different populations (Jambuthenne et al, 2022; Wang et al, 2021; Yang et al, 2020; Yao et al, 2021). The APR gene Yr29 was also mapped in this region (Rosewarne et al, 2006), but it is only distributed in the varieties from Sichuan, Henan and Shandong (Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of resistant landraces is variable, depending on many factors such as the plant stage, type of inoculation (natural or artificial), and the race of the pathogen, but normally, the frequency of resistance ranges 5-30% of the total number of landraces [30][31][32][33]. Selection for rust resistance in wheat landraces collections may currently be assisted by the use of DNA markers linked to different R-genes, and even genome-wide association analysis can be performed [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%